(untitled) (Proceedings of International Conference on Special Education, 2017)
Thai society became aware of Inclusive Education only through the influence of law and regulations. Schools and teachers played a significant role in supporting special educational needs (SEN) students. This research project aspires to learn more in- depth about how inclusive schools are run, through studying: 1) the teachers’ complications when working with SEN students in inclusive schools; and, 2) the needs of the teachers to be supported while working with SEN students. This qualitative study was conducted in Lopburi Province by using SEAT framework to acquire the data. Eleven pilot-project inclusive schools in Lopburi Province were selected to be fieldwork sites for the research project. Paper documents, classroom observations and in-depth interviews with the teachers were completed in order to triangulate the source of data. The results from visiting school participants revealed four different main themes ranging from: 1) what teachers implemented for inclusive classrooms: teachers’ training, screening process, individualized education plan (IEP) process, teaching process, and supervising; 2) the other stakeholders’ backing off: supporting and funding; 3) how SEN students are being included in inclusive classrooms, being supported by the schools, their development, career paths, and referral for higher levels of education; 4) the teachers’ suggestions for effective inclusive classrooms.